2018
DOI: 10.1186/s41610-018-0069-0
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, abundance, and effect on plant species diversity of Sasa borealis in Korean forests

Abstract: Background: Sasa borealis (Hack.) Makino, a clonal dwarf bamboo, is widespread in Korean forests. Although S. borealis is native to that country, its growth habit can cause considerable harm when occupying particular areas where it dominates and influences those forested communities. However, few reports have described the extent of its inhibitory effects on the vigor of co-existing plant species. Therefore, we investigated the distribution, abundance, and diversity of other plant species in the communities wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Deogyu (from 600 to 1400 m, 2.4 km long) and Sobaek (from 870 to 1100 m, 1.4 km long). Consistent with the results of Cho et al (2018), it was distributed mainly in the late-successional forests where Q. mongolica dominated. In fact, S. borealis flourishes as if there are virtually no limitations.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Deogyu (from 600 to 1400 m, 2.4 km long) and Sobaek (from 870 to 1100 m, 1.4 km long). Consistent with the results of Cho et al (2018), it was distributed mainly in the late-successional forests where Q. mongolica dominated. In fact, S. borealis flourishes as if there are virtually no limitations.…”
Section: Discussionsupporting
confidence: 87%
“…They have been known to be species that inhibit species diversity and tree regeneration (e.g., Nakashizuka and Numata 1982;Ito and Hino 2007;Cerny et al 2013Cerny et al , 2015. Cho et al (2018) reported that plant species diversity was significantly reduced with the dominance of Sasa borealis in the forests of Gangwon Province, Korea. Due to the clonal growth habit, it forms a dense mono-stand that physically occupies the aboveground and underground spaces and lowers the light intensity reaching the floor (Wada 1993;Park et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, dwarf bamboo (Sasa spp.) possesses the chief competing role in the understory of Far East temperate forests, hence, largely controlling forest dynamics and structure [76,86,87].…”
Section: Vegetation Changes After Typhoonsmentioning
confidence: 99%
“…The bulb of E. japonicum is buried about 12 cm below the ground surface (Lyang and Lee 2010), and it could be the reason why the wild boar dug deeper in the Quercus forest type than other forest types. The wild boar digs even Sasa borealis stands in the Quercus forest, which is dominated by S. borealis and has very low species diversity (Cho et al 2018a(Cho et al , 2018b. The food sources such as acorns and insects for the wild boar are presumably between the packed roots or dense culms of S. borealis.…”
Section: Quercus Forest Preference Of Wild Boarmentioning
confidence: 99%